Disease as a Factor in the Demise of the Beothuck Indians - Marshall, Ingeborg (Culture)

(untitled) (Canadian Anthropology Society / Société Canadienne d’Anthropologie (CASCA), formerly/anciennement Canadian Ethnology Society / Société Canadienne d’Ethnologie, 1981)
After 330 years of European exploration and settlement on the island of Newfoundland, the Beothuck Indian population became extinct. In order to establish how far the demise of these Indians was due to diseases introduced by the Europeans, bubonic plague, smallpox, measles and tuberculosis, these are considered in relation to the changing circumstances of the Beothucks and their patterns of contact with each other and with the European settlers. The effect of these diseases on Beothuck demography is discussed using documentary evidence of disease incidence in the Newfoundland population as well as comparative data from other North American Indian groups.